The Influence of Organizational Culture on the Skills and Creativity of Generation Z Employees - Ardiansyah, Muhammad Eka; Ribhan, Ribhan; Safitri, Dina (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Organizational culture plays an essential role in shaping employee behavior, skills, and creativity, particularly among Generation Z, who dominate today’s digital workforce. This study aims to analyze the influence of organizational culture on the skills and creativity of Generation Z employees in the creative industry. The research employed a quantitative approach with a causal design and survey method. Data were collected from 111 Generation Z employees working in creative industry subsectors in Bandar Lampung. A structured questionnaire was used as the research instrument, and the data were analyzed using multiple linear regression with SPSS 24. The results indicate that organizational culture has a positive and significant effect on employee skills and creativity). These findings highlight that a strong organizational culture enhances both skills and creativity among Generation Z employees.